2023
DOI: 10.4103/aja202315
|View full text |Cite
|
Sign up to set email alerts
|

Low XIST expression in Sertoli cells of Klinefelter syndrome patients causes high susceptibility of these cells to an extra X chromosome

Abstract: Klinefelter syndrome (KS) is the most common genetic cause of human male infertility. However, the effect of the extra X chromosome on different testicular cell types remains poorly understood. Here, we profiled testicular single-cell transcriptomes from three KS patients and normal karyotype control individuals. Among the different somatic cells, Sertoli cells showed the greatest transcriptome changes in KS patients. Further analysis showed that X-inactive-specific transcript (XIST), a key factor that inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…In addition, tremor is the first and most frequent symptom in male patients with SBMA, but less frequent in female patients (10). In the current patient, only mild muscle spasms and muscle twitching were observed before the initiation of androgen replacement therapy, which is similar to the symptoms observed in female carriers (8,11). Furthermore, although it was reported that a decrease in serum creatinine levels precedes the onset of motor symptoms by approximately 15 years in male patients with SBMA, no decrease in serum creatinine levels was observed in this patient.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, tremor is the first and most frequent symptom in male patients with SBMA, but less frequent in female patients (10). In the current patient, only mild muscle spasms and muscle twitching were observed before the initiation of androgen replacement therapy, which is similar to the symptoms observed in female carriers (8,11). Furthermore, although it was reported that a decrease in serum creatinine levels precedes the onset of motor symptoms by approximately 15 years in male patients with SBMA, no decrease in serum creatinine levels was observed in this patient.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, the initiation of testosterone replacement therapy in this patient may have caused an earlier and more severe onset of symptoms by promoting a higher degree of nuclear translocation of the abnormal AR protein bound to testosterone. Although it was reported that excess X chromosome inactivation occurs in the majority of cells in Klinefelter syndrome (11,12), 15%-30% of the genes on the inactivated X chromosome escape inactivation (13). At this time, the extent to which the AR gene is expressed or inactivated in patients with Klinefelter syndrome is unknown.…”
Section: Discussionmentioning
confidence: 99%